Development of Physics Learning E-Module for Class X High School Students - Nur Indriati Harahap; Ramalis Hakim; Rayendra; Ridwan (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the validity of the physics e-module for grade X Senior High School students. The type of research used is research and development (R&D) by adopting the ADDIE development model. The stages of the ADDIE development model consist of Analysis, Design, Development, Implementation, and Evaluation. Data analysis was conducted to assess the validity of the physics e-module in three aspects: media, content, and language. Validity was evaluated by six experts: two media experts, two content experts, and two language experts. The results of the validity test of the physics e-module obtained from media experts was 79% with the category "Valid", from content experts was 94% with the category "Very Valid", and from language experts was an average of 90% with the category "Very Valid". It can be concluded that the physics e-module is valid and suitable for use in physics learning for grade X Senior High School students.